Determinan Penyalahgunaan Aset dalam Perspektif Fraud Hexagon di RSUD Jawa Barat - Ruri Octari Dinata; Yasinta, Yasinta Rizki Amalia (Politeknik Ganesha Medan, 2024)
The aim of this study is to gather empirical data regarding asset misappropriation motivated by fraud hexagons (pressure, opportunity, rationalization, capability, arrogance, and collusion) in West Java Hospital. Purposive sampling was utilized as the sampling technique for this quantitative investigation, while primary data were collected by distributing questionnaires. 61 personnel of West Java Hospital has became the study's sample. The sampling design used is non-probability sampling from purposive sampling. Multiple regression analysis is the technique for data analysis, and IBM SPSS Statistic 26 is used to handle it. Based on the study's results, asset misappropriation is influenced positively by factors such as pressure, opportunity, and capability. However, arrogance and variable rationalization do not have any effect on asset misappropriation.. Contrarily, collusion has a negative impact on asset theft. This research possesses various constraints that should be acknowledged. Firstly, due to time constraints during the study, the researchers were unable to include a diverse and extensive population sample. Secondly, the distribution of questionnaires was done directly, resulting in a considerable amount of time consumption. Lastly, as the hexagon theory is a recent development, there is a scarcity of comparative references available, further limiting the scope of the study. For future research, it is recommended to distribute questionnaires online to expand the range of population areas and research samples to obtain more information and data.